Caracterização de lipopeptídeos antimicrobianos e surfactantes produzidos por Bacillus spp. isolados de puba - Karla Joseane Perez (2014)
Naturally fermented foods like cassava puba are sources of microorganisms able to produce antimicrobial compounds. Several products of industrial interest are produced by Bacillus whichinclude enzymes, antibiotics, aminoacids, insecticides, biosurfactants and bacteriocins. In this study biosurfactants and antimicrobial substances produced by Bacillus spp. (5 C3 and P5) isolatedfrom the food matrix Puba were characterized, and the one with higher antimicrobial activity was chosen for further testing. The identification of both bacteria was performed by phenotypic, chemotaxonomic and genotypic tests, and the resultsindicated that they belong to the genusBacillus and Bacillus sp. C3 to B. cereus/B. thuringiensis and Bacillus sp. P5 to the species Bacillussubtilis/amyloliquefaciens. The spectrum of antimicrobial activity was assessed using microorganisms (45) which included Gram-positive and Gram-negative bacteria, filamentousfungi and yeasts, and activity against 62% (28) of the test organisms was observed. An increase in antimicrobial activity was detected when Bacillus sp. P5 was cultured with inactivated cells of other microorganisms, but not when in contact with the supernatant of these, with higher activities for Corynebacterium fimi, Aspergillus fumigatus, Lactobacillus brevis E4-248, Lactobacillus fermentumE4-249 and Lactobacillus plantarum EPF-257. These results indicate that there isinterference of quorum-sensing inducing factors, especially when the microorganisms were from the natural microbiota of this fermented food, increasing the production of the antimicrobialsubstance(s) by Bacillus sp. P5. The crude supernatant of Bacillus sp. P5 showe bacteriostatic action against Bacilluscereus ATCC 14579 and against Listeria monocytogenes ATCC 6477. The characterization of biosurfactant activity was detected by beta hemolysis zone around the colony, by emulsifying activity tests and the measurement of the surface tension. Emulsifying activity of the supernatant was observed for all the tested substances (4), with the exception of xylene, which is capable of forming emulsion only when tested in the supernatant medium Landy with glutamate. Reduction of the surface tension of the culture medium was also observed, suggesting the production of surface-active compounds by the bacteria. The PCR followed by sequencing of amplicons allowed the identification of genes related to the synthesis of the bacteriocins subtilosin A and subtilin for Bacillus sp. C3 constituting the first record of the presence of these genes for Bacillus thuringiensis/B. cereus species, which possibly belongs toBacillus sp. C3. Regarding Bacillus sp. P5, subtilosin A, surfactin and iturin A were identificated. Among the techniques employed for purification, the best results were seen with butanol extraction followed by reverse phase chromatography on C18 column and HPLC coupled to MALDI-TOF mass spectrometry for analysing culture supernatant. Foranalyzing the substances directly into the food matrix,by reverse chromatography was replacedby an adapted method of extraction with butanol using a C4 column (zip tip). The isolated Bacillus sp. P5 is able to coproduce five (5) different types of lipopeptides (surfactin, fengicin, iturin, micosubtilin and bacilomicin) and therefore presents varied activity of biocontrol. Furthermore, this study demonstrated the high production of different isoforms of surfactin (C13 - C17) in the culture medium, including the C15 isoform, the most biologically active isoform, and C17, rarely described as well as the first detection of lipopeptides as fengicin and iturin directly in manioc food matrix. This food is widely consumed by populations in northern and northeastern Brazil and the knowledge about these substances could contribute to increased food safety and shelf life of this type of food.